(untitled) (Research, Society and Development, 2021)
Laboratory analysis has an impact on the different stages of health: prevention, diagnosis, prognosis and therapeutic. Blood samples were collected from quilombolas representatives of the two communities. The samples were stored with anticoagulants (EDTA and fluoride) and without anticoagulant. Were performers the laboratory tests (blood count, lipidogram, urea, creatinine, glycemia and vitamin D). The results showed that 22% of the quilombolas presented values of glycemia among 100 and 126 mg dL. Results of the lipidogram test showed 24.4% presented triglyceride variation above 150 mg / dL; 57.7% presented cholesterol above 190 mg / dL; 35.5% had HDL levels below 40 mg / dL and 66.6% had LDL levels above 110 mg / dL. Regarding the hemogram, 15.5% of the hematocrit tests and 24.4% of the hemoglobin tests were found, with values lower than the reference values. Vitamin D presented 40% of patients with values below 30 ng / mL. Glomerular filtration rate calculations showed that 66.66% presented among mild to severe changes in renal filtration rate. The data obtained, show that was possible to highlight that among the quilombolas, there are metabolic disorders of carbohydrates, lipids and vitamin D, which correlate with changes in BMI, justifying cases of overweight.